Early Muslim scholarship in religionswissenschaft : the works and contributions of Abu Rayhan Muhammad Ibn Ahmad Al-Biruni - Kamaruzaman, Kamar Oniah (ISTAC, International Islamic University Malaysia, 2003)
This book presents early Muslim scholars and their scholarship on study of other religions. The focus of this book is on al-Biruni, his life and works on the study of other religions, his methodologies, his special contributions in Comparative Religion. This book propunds that al_biruni be proclaimed "the Father of Comparative Religion"